Effect of the Pes Planus on Vertical Jump Height and Lower Extremity Muscle Activation in Gymnasts - Tamer Çankaya; Nurcan Contarlı (Selcuk University, 2022)
Gymnastics is an aesthetic olympic branch where systematic and rhythmic movements are performed at high levels in harmony with the body (19). It is a popular sport requires a combination of physical fitness components such as speed, agility, strength, balance and flexibility. Especially, lower extremity alignment can affect successful performance in gymnasts (6). Pes planus is generally defined as a postural disorder caused by lowering or absence of the medial longitudinal arch height of the foot (17). Although there are many studies that try to explain the cause of pes planus; a clear etiological cause, which is accepted and agreed upon today cannot be presented (9,11,23,27). For the diagnosis of pes planus; clinical measurement and examination, radiological and ultrasonographic methods are used. In addition, it was evaluated with methods such as ink footprint methods, digital pressure measurements and podoscope (22,24). Calculations such as Clark angle, Chippaux-Smirak Index and Shateli Index are used in the evaluation of pes planus (22). The muscle function of the lower extremity is affected by the structure of the foot. In a foot with pes planus, the load on the foot cannot be evenly distributed. Therefore, muscles and other structures provide compensation to meet this irregularity. In the studies on pes planus, EMG method was used to investigate the structural deformity of the foot and the changes in the activities of the lower extremity muscles during walking or jumping (10,12,15,16). Electromyography (EMG) is the science of recording and interpreting the electrical activity of muscles. In recent years, EMG studies have provided an important perspective in understanding muscle functions and have been accepted as the golden key in recording muscle activity (25). Surface electromyography (sEMG) is used to examine the neuromuscular activation of the muscles that function in functional movement, balance-related situations and in the training of athletes (4,13). Jumping is a movement that an individual has made against his or her own body weight. Jumping performance depends on features such as muscle strength, explosive speed, flexibility, body anthropometry and motor coordination (8,18). Jumping is an important motor skill in all gymnastics disciplines and has a decisive role in performance (18). This study aims to determine the effect of the presence of pes planus on vertical jump height and muscle activation in gymnasts.